PISA-LIKE PROBLEMS USING ISLAMIC ETHNOMATHEMATICS APPROACH - Muhammad Win Afgani; Retni Paradesa (Jurnal Infinity, 2021)
The study aimed to produce PISA-like mathematics problems with the Islamic ethnomathematics approach that were valid and practical. A development study with formative evaluation was used as the method in this study with 32 9th-grade students as the subjects at one of the junior high schools in Palembang, South Sumatra province, Indonesia. There are five phases: self-evaluation, expert review, one-to-one, small group, and field test. Interviews, questionnaires, and tests were used in this study as the instruments to collect the data. The results showed that three experts from the expert review phase assess that 77.78% agree that six PISA-like mathematics problems meet the validity criteria. For the practicality criteria, three students from the one-to-one step set about 77,78% agree, three students from the small group phase assessed about 61,11% strongly agree, and 26 students from the field test phase considered 61,33% agree. This result is supported by the average test result that was classified as a low category. This showed that the results obtained are not optimal because students still did not understand the problems and had difficulty solving them.